Poverty among Foster Children: Estimates Using the Supplemental Poverty Measure - Pac, Jessica (Soc Serv Rev, 2017)
We use data from the Current Population Survey and the new Supplemental Poverty Measure (SPM) to provide estimates for poverty among foster children over the period 1992 to 2013. These are the first large-scale national estimates for foster children who are not included in official poverty statistics. Holding child and family demographics constant, foster children have a lower risk of poverty than other children. Analyzing income in detail suggests that foster care payments likely play an important role in reducing the risk of poverty in this group. In contrast, we find that children living with grandparents have a higher risk of poverty than other children, even after taking demographics into account. Our estimates suggest that this excess risk is likely linked to their lower likelihood of receiving foster care or other income supports.